Konvergensi Komunikasi Pelaku Pelestarian Sumber Daya Genetik di Kota Sawahlunto - Yessi Arza; Yenny Oktavia; Sri Wahyuni (Syntax Corporation, 2023)
The study aims to analyze the convergence of communication between actors conserving genetic resources of Kubang durian. This study used a qualitative descriptive approach. The convergence of communication between conservation actors is reviewed based on three aspects, namely mutual understanding, mutual agreement and joint action. The mutual understanding between Kubang durian conservation actors can be seen from the understanding between conservation actors about Kubang durian, which is the icon of Kubang durian, has a distinctive taste and is endangered. The mutual agreement between Kubang durian conservation actors is reflected in the agreement to carry out the registration and release of Kubang durians with the Decree of the Mayor of Sawahlunto Number 188.45/239/WAKO-SWL/2020 concerning the Appointment and Determination of the Excellence and Truth Test Team and Farmers Implementing the Registration and Release of Kubang Durian in Sawahlunto City. Joint action is reflected in the exploration and registration and release of Kubang durian. Communication convergence in the exploration stage does not occur in all actors. This is due to the lack of information sharing, lack of interaction and dialogue between conservationists. Communication convergence in the release stage of the Kubang durian variety also did not occur in all actors. This is due to differences in understanding between conservationists about the criteria for superior durians for the release of varieties.